2017
DOI: 10.1186/s12879-017-2839-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of influenza in West Africa after the 2009 influenza A(H1N1) pandemic, 2010–2012

Abstract: BackgroundOver the last decade, capacity for influenza surveillance and research in West Africa has strengthened. Data from these surveillance systems showed influenza A(H1N1)pdm09 circulated in West Africa later than in other regions of the continent.MethodsWe contacted 11 West African countries to collect information about their influenza surveillance systems (number of sites, type of surveillance, sampling strategy, populations sampled, case definitions used, number of specimens collected and number of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…In mild cases of infection (ILI), the frequency of influenza cases was 24.8% as compared to 18.7% in severe cases (SARI). Higher proportions of positive influenza cases in ILI as compared to SARI have as well been reported by Mainassara et al in Niger as well as several other West African countries [8, 12, 13]. We noted that lower influenza positivity rate in SARI patients could be attributed to delayed presentation in hospitals resulting in reduced viral loads and lower detection rates as suggested by Dalhatu et al [8].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In mild cases of infection (ILI), the frequency of influenza cases was 24.8% as compared to 18.7% in severe cases (SARI). Higher proportions of positive influenza cases in ILI as compared to SARI have as well been reported by Mainassara et al in Niger as well as several other West African countries [8, 12, 13]. We noted that lower influenza positivity rate in SARI patients could be attributed to delayed presentation in hospitals resulting in reduced viral loads and lower detection rates as suggested by Dalhatu et al [8].…”
Section: Discussionsupporting
confidence: 83%
“…These results are contradictory to reports from Manirakiza et al in Central Africa Republic where infants aged 0–6 months (8.8%) and people aged 15–50 years (11.0%) had higher proportions of influenza cases [11]. A similar report by Nzussouo et al from West African countries reported that majority of ILI and SARI case-patients testing positive for influenza viruses were children aged 0–4 years [12]. In the latter, higher rates of influenza-associated illness in the 0–4 years age group can be attributed to a selection bias since more than 70% of samples collected were from children aged 0–14 years.…”
Section: Discussionmentioning
confidence: 59%
“…Seasonality patterns of influenza in eastern Africa including Ethiopia, have not been clearly established [13]. However, some evidences from different studies indicated that Influenza A (H1N1) pdm2009, Seasonal Influenza A (H3N2) and Influenza B are circulating in different countries of sub-Saharan Africa [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many avian and several mammalian species are susceptible to IAV infections with varying degrees of morbidity and mortality. Among humans, annual influenza morbidity and associated mortality are estimated at 3-5 million and 250,000-500,000, respectively (Talla Nzussouo et al, 2017). In swine, IAV infections cause mild respiratory disease which may predispose to opportunistic bacterial infections causing reduced weight gain during the fattening period and leading to substantial losses in pork production.…”
Section: Introductionmentioning
confidence: 99%